Soveltavan kielitieteilijän sormenjälkiä etsimässä - Aarikka Lotta; Priiki Katri; Ivaska Ilmari (Suomen soveltavan kielitieteen yhdistys AFinLA ry, 2025)
This section introduces the collective volume that honours the memory of our esteemed colleague Kirsti Siitonen who contributed to the study of Finnish language on various branches. She was a pioneer especially in Finnish L2 research but also studied Finnish dialects and pronoun variation. The collective volume introduces new studies that build on Siitonen’s work. In this introduction we reflect what kind of resemblances the research topics presented in this volume have to each other and to Siitonen’s studies. Siitonen often approached the variation between L1 and L2 and in different dialects by investigating a certain structure. The result is a many-sided collection that aims at crossing boundaries between disciplines.